Effects of theTiB2-SiC Volume Ratio and Spark Plasma Sintering Temperature on the Properties and Microstructure of TiB2-BN-SiC Composite Ceramics - Shi Tian; Zelin Liao; Wenchao Guo; Qianglong He; Heng Wang; Weimin Wang (Crystals, 2021)
TiB2-BN composite ceramics combine excellent electrical conductivity, thermal shock resistance, high-temperature resistance, corrosion resistance, and easy processing of TiB2 and BN. However, in practical applications, their high-temperature oxidation resistance is poor and the resistivity distribution is uneven and changes substantially with temperature. A TiB2-BN-SiC composite ceramic with stable and controllable resistivity was prepared by introducing SiC into the TiB2-BN composite ceramics. In this work, spark plasma sintering (SPS) technology was used to prepare TiB2-BN-SiC composite ceramics with various TiB2-SiC ratios and sintering temperatures. The samples were tested by XRD, SEM, and thermal and mechanical analysis. The results show that as the volume ratio of TiB2-SiC was increased from 3:1 to 12:1, the resistivity of the sample decreased from 8053.3 to 4923.3 μΩ·cm, the thermal conductivity increased from 24.89 to 34.15 W/(m k), and the thermal expansion rate increased from 7.49 (10−6/K) to 10.81 (10−6/K). As the sintering temperature was increased from 1650 to 1950 °C, the density of the sample increased, the mechanical properties were slightly improved, and the resistivity, thermal expansion rate, and thermal conductivity changed substantially. The volume ratio and sintering temperature are the key factors that control the resistivity and thermal characteristics of TiB2-SiC-BN composite ceramics, and the in situ from liquid phases of FeB and FeO also promotes the sintering of the TiB2-BN-SiC ceramics.